Russian and Chinese Natural Gas Industries: Perspectives on Sustainable Growth. Issue 15 (10th December 2019) - Wang, Zhen; Kleiner, George; Bragina, Zinaida; Denisov, Artem; Steblyanskaya, Alina
ABSTRACT: The influence of an investment in social well-being and environmental protection on the steady financial growth of the oil and gas industry is studied, and a new interpretation of financial growth is proposed. Unlike traditional approaches to this interpretation, the proposed interpretation views financial growth as a function of energetic, ecological, economic, and social factors. The composition and the structure of steady financial growth are considered for Russian and Chinese oil and gas companies. The Lasso regression, linear regression and SARIMA modelling are used for determining the composition of economic processes affecting or predetermining the Sustainable Growth Rate up to the year 2030. The presence of a close dependence among the dynamics of energetic, social, and financial processes and the absence of a close dependence between the dynamics of financial growth and the values of environmental protection indices are established for Russian oil and gas companies. On the contrary, the close dependence between the dynamics of financial growth and the values of environmental protection indices and energetic activities, and the absence of a close dependence between the financial growth and the social well-being of the personnel are determined for Chinese oil and gas companies.